The Effect of Facilities and Infrastructure Management on The Quality Of Learning at SMP Negeri 1 Parigi - Mutiara Anjani; Annisa Nurahmayanti; Laelatul Mutmainah; Ujang Saepul Milah; Yayat Hidayat (Journal of Studies in Academic, Humanities, Research, and Innovation, 2025)
This study aims to analyze the influence of facility and infrastructure management on the quality of learning at SMP Negeri 1 Parigi. Adequate facilities and infrastructure play a very important role in creating a conducive learning environment, which in turn affects the quality of learning. The method used in this study is a qualitative descriptive approach, with data collection through observation and interviews with teachers, students, and school administration staff. The results of the study show that good management of facilities and infrastructure has a positive effect on the comfort and effectiveness of the learning process. Adequate facilities, such as comfortable classrooms, complete teaching aids, and other supporting facilities, increase interaction between teachers and students, which ultimately affects the improvement of learning outcomes. However, this study also identified shortcomings in the management of facilities, such as less modern equipment and the mismatch of the number of facilities with the number of students. The implication of this finding is the need to improve the management of facilities and infrastructure at SMP Negeri 1 Parigi, as well as to improve coordination between the school and the government to optimize existing facilities. This research is expected to provide insight and basis for better management of facilities and infrastructure, so that it can improve the quality of learning in schools.